A study on diabetes mellitus among diabetic foot ulcer patients in a tertiary care centre - Gopinath, Vinu; Rajan, S. Soundara (International Surgery Journal, 2017)
Background: Diabetes mellitus is a chronic disease which occurs either when the pancreas does not reproduce enough insulin, the hormone that regulates blood sugar level or when the body cannot effectively use the insulin it produces. Hyperglycemia or raised blood sugar level is a common effect of uncontrolled diabetes and over time leads to serious damage to many of the system of the body especially nerves and blood vessels. Diabetes mellitus has become the cause for growing public health concern in developing countries as it has been for a long time in most developed ones. The reason for increase in prevalence of diabetes mellitus in developing countries may include unhealthy life style, rapid westernization, poor knowledge, negative attitude and poor practice towards diabetes mellitus among general population. Objective of the study was to find out the knowledge, and awareness towards diabetes mellitus among diabetic foot ulcer patients attending in a tertiary care Centre. Methods: A cross sectional study was carried out in the surgical outpatient department of a tertiary care Centre. All diabetic foot ulcer patients attending surgical outpatient department for the period of two months was included. Juvenile diabetic patients, Type II diabetes mellitus patients with co morbidities are excluded. Results: Out of the 100-study participant’s majority are males (61%). 55% of the study participants are not aware of the major cause of diabetes mellitus. 92% of the population knew the accurate method of monitoring diabetes mellitus. 70.6% of people are aware of normal blood sugar level. 51% of people are aware of the complications of diabetes mellitus and 84.3% of people know the symptoms of diabetes mellitus. 68.6% of the population knew regular exercise can control diabetes mellitus yet only 50.8% of population exercise regularly. Conclusions: This study reflects that there is a need to improve diabetic knowledge among the patients which can be achieved through health education.